Cytokines Profile in Patients with Acute Myocardial Infarction - Al-Hassan, Ahmed Abdul-Hassan Abbas (Al-Nahrain Journal of Science, 2012)
A total of 30 acute myocardial infarction patients and 30 age and sex-matched healthy controls were enrolled in this study. Patients group showed significant increase in serum levels of IL-1α, IL-2 and IL-6 as compared with controls (p<0.01 and P<0.05), and no statistically significant changes were found in serum levels of IL-4 and IL-10 between patients and controls. On the other hand there was positive linear correlation between IL-1α and IL-6 (r=0.787; P=0.004) and negative linear correlation between IL-10 and IL-6 (r=-0.601; P=0.049) in patients with acute myocardial infarction. In conclusion, the present study showed an increase production of pro-inflammatory cytokines and decrease production of anti-inflammatory cytokines in acute myocardial infarction patients.